Domestic Tourists' Perceptions of Kelan Beach Attributes, Badung - Bali - Ni Kadek Widya Wijayaningtyas; Luh Nyoman Tri Lilasari; Anom Hery Suasapha (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to evaluate domestic tourists' perceptions of the quality of Kelan Beach attributes and to group these attributes. The data analysis methods used are descriptive statistical analysis and exploratory factor analysis. The type of data used is quantitative data with a non-probability sampling technique of 100 respondents. The results show that the attributes